Non-people in the People’s Republic: ‘Landlords’ and ‘rich peasants’ under Maoist state socialism - Czeller, MA (2022)
For some thirty years, a substantial minority of the Chinese population was excluded from the political and moral community of the People. The largest number of non-People were the only literal ‘class’ enemies in the People’s Republic: those labelled ‘landlords’ and ‘rich peasants’ during land reform by reference to their socioeconomic position in rural society before the revolution. This thesis is a political, cultural, and social history of this group. It approaches the ‘landlord-rich peasant question’ as a single subject, one which originated in the 1920s, was central to politics, culture, and social life in the Mao era, and which, in a number of sometimes unexpected ways, continued well into the Reform era.